The Risk of Bullying as a Result of COVID-19 among University Students - Alrawashda, Maissa Nasser (Opción, 1970)
This Article is aimed to reveal the types and levels of bullying towhich undergraduate Asian students are exposed to because of theCOVID-19 pandemic. By applying the Multidimensional BullyingVictimization Scale to (202) students of Asian nationalities(Indonesian, Uzbek, Thai, Filipino, Chinese) who are pursuing theiruniversity education in Governmental universities. The results foundthat Asian male and female students have encountered four types ofbullying: Relational Bullying, Cyber Bullying, Physical Bullying andRace and Culture-based Bullying. Cyber bullying was the mostcommon type of bullying among students. The results also revealedthat the Chinese students are the students who faced most bullying,followed by the Indonesian students, respectively, while the Filipinostudents are the students experience the least bullying as a result of theCOVID-19 pandemic.